The Houstiliad : An Iliad for Houston - Lieberman, Michael, 1941- (Book collections on Project MUSE., 2015)
"In this nervy adaptation of Homer's classic, the story of Achilles' rage is told with a deft touch and a large dollop of humor. Achilles, an MIT-trained engineer, has dropped out and with Patroclus, his white macaw, cruises around Houston on an old BMW motorcycle looking for trouble. And he finds plenty. Along the way we meet Hector, the Hammer; Agamemnon, a wealthy Houston businessman with an eye for Achilles' girlfriend; Aphrodite, a custom bra designer; Apollo, owner of Cafe Apollo; and many of Homer's other characters, as Lieberman liberates them from their classical context. The result is a wry take on Houston and an uncompromising exploration of the rage of men in contemporary society"--ECIP Summary